Childhood Maltreatment Is Associated With Aggression Among Male Juvenile Delinquents in China: The Mediating Effects of Callous-Unemotional Traits and Self-Control - Xie, Qinhong; Bi, Taiyong; Du, Yan; Kou, Hui; Yang, Bo (Frontiers in Psychology, 2020)
Background: Aggression is an important risk factor for delinquency and crime in adolescents. Previous studies have indicated that childhood maltreatment plays an important role in the development of aggression. However, whether the effect could be mediated by other factors is still unknown. Evidence suggests that callous-unemotional (CU) traits and self-control may be candidate mediators in the relationship between childhood maltreatment and aggression. Methods: A total of 585 male juvenile delinquents from China were recruited for the present study. We measured self-reported childhood maltreatment, CU traits, self-control and aggression with the short form of the Childhood Trauma Questionnaire, the Inventory of Callous-Unemotional Traits, the Self-Control Scale and the Aggression Questionnaire, respectively. Furthermore, we constructed multiple mediation models to investigate the mediating effects of CU traits and self-control on the relationship between childhood maltreatment and aggression. Childhood maltreatment and aggression were entered into the model as the independent and dependent variables, respectively, and CU traits and self-control were treated as the mediating variables. In addition, the moderating role of self-control in the relationship between childhood maltreatment and aggression was tested by constructing a moderation model. Results: Correlation analysis showed significant positive correlations among childhood maltreatment, CU traits and aggression (all r values>0.31, P values<0.01), while self-control was negatively correlated with these three factors (all r values<-0.32, P values<0.01). Mediation analyses showed that the relationship between childhood maltreatment and aggression was completely and sequentially mediated by the factors of CU traits and self-control (indirect effect=0.31, P<0.001). In addition, the relationship between childhood maltreatment and aggression could also be completely mediated by CU traits (indirect effect=0.24, P<0.001) and self-control (indirect effect=0.26, P<0.001) separately. Conclusion: Our results indicate that childhood maltreatment impacts aggression only through the mediation of CU traits and self-control, which may shed light on the development of aggression among male juvenile delinquents.